Comparison of arthroscopic and open Brostrom-Gould surgery for chronic ankle instability: a systematic review and meta-analysis - Binzhi Zhao; Qingnan Sun; Xiaopei Xu; Yang Liu; Yanrui Zhao; Yulin Gao; Junlin Zhou (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background Approximately 20% of acute ankle sprains progress to chronic lateral ankle instability (CLAI) requiring surgical intervention. There has been growing interest among surgeons regarding whether arthroscopic techniques can replace open Brostrom-Gould surgery in treating CLAI. The purpose of this study was to pool the results of multiple studies comparing the treatment effects of these two fixation approaches. Methods Our study involved thorough searches across multiple electronic databases, including PubMed, Cochrane, Embase, and Web of Science, to identify all relevant publications on CLAI that were repaired using the arthroscopic or open Broström-Gould technique. Through a comprehensive meta-analysis, we evaluated several outcomes, including post-operative function, radiological measurements, complications, and time efficiency. Result A total of 686 patients from 11 studies were included in the analysis. Among them, 351 patients underwent open repair, and 335 underwent arthroscopic Brostrom-Gould surgery. The present study revealed that arthroscopic and open Brostrom-Gould techniques demonstrated no significant differences in talar tilt, talar anterior translation, complication rate, and time to return to previous level of activity. Furthermore, no significant differences were observed in AOFAS, K–P, VAS, and Tegner scores at the 2-year follow-up. However, significant differences were noted between the two surgical approaches in terms of early weight-bearing (WMD = − 1.33 weeks, 95% CI = [− 1.91, − 0.76], P = 0.17, I2 = 40%), as well as AOFAS scores (WMD = 1.00, 95% CI = [0.05, 1.95], P = 0.73, I2 = 0%), K–P scores (WMD = 1.57, 95% CI = [0.49, 2.64], P = 0.15, I2 = 47%), and VAS scores (WMD = − 0.15, 95% CI = [− 0.60, 0.29], P < 0.08, I2 = 61%) within the first postoperative year. Conclusions Our findings support that arthroscopic repair yields comparable outcomes to open surgery. Consequently, we advocate for adopting arthroscopic repair as a preferred alternative to the conventional open Broström-Gould procedure for treating chronic lateral ankle instability.